Analysis on the application of investments in water losses in Northeast Brazil - Cambrainha, Géssika Maria Gama; Fontana, Marcele Elisa (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2015)
The sanitation situation across Brazil is considered calamitous. Due to the geographical characteristics of the Northeast region, the water found in this state needs to be harnessed to the fullest. One way to achieve this goal is through the control of water loss. The present study aimed to evaluate how much of the investment in the water sector is reflected in reduced losses. More specifically the objectives were: (1) Collect information and investment losses in the water sector in the Northeast region; (2) Perform diagnosis of loss of water in the Northeast; (3) Perform statistical analysis. By examining the high rates of loss, it is evident that increased investments in large projects for increased capture of water resources is the focus of the companies, while the proper management of the losses, with which the northeastern states could avoid constant dependence on climate, is not treated as a primary goal.